Contributing Factors of Personal Protection Equipment (PPE) Utilization among Sand and Gravel (SSG) Mine Workers - Tristiana, Rr Dian; Pravitasari, Ratih; Wahyuni, Erna Dwi (International Journal of Psychosocial Rehabilitation, 2020)
The low utilization of personal protection equipment (PPE) can cause a high rate of work accidents. The contributing factors related to PPE utilization need to be explored. This study aimed to explore the contributing factors of personal protection equipment utilization among sand and gravel mine workers. This study was cross-sectional. A total of 118 respondents participated in this study. The independent variables were belief, knowledge and the attitude of the sand and gravel miners, the availability of PPE and employee attitude. The dependent variable was the sand workers’ behavior in using the PPE. The data were collected using a questionnaire, and tested using Spearman Rho test with a significance level of p <.05. The results showed that the workers’ belief affected their preference related to using PPE (p=.029; r=.202). The workers’ good understanding was also shown to have a positive effect on using PPE (p=.000; r= 0,669). On the other hand, the availability of PPE (p=.000; r=.328), the site owners’ awareness, and peer support were known to have no significant effect on influencing the workers’ behavior in using PPE while at the mining sites (p=0.917). Knowledge was the strongest influencing factor. Counseling, training, and motivation regarding the use of PPE should be conducted in order to improve the sand and gravel miners’ knowledge and positive attitude toward using PPE.